Optimize Thermal Management And Experiment Of Lifepo4 Battery Pack For Hybrid Electrical Vehicle - Abdul Muchlis; Moh. Yamin (International Journal of Science, Technology & Management, 2021)
Hybrid Electric Vehicles (HEV) combines the benefits of gasoline engines and electric motors which can be configured for improving fuel efficiency. Lithium Iron Phosphate (LiFePO4) Phosphate based technology possesses superior thermal and chemical stability which provides better safety characteristics than those of Lithium-ion technology made with other cathode materials. This research conducted by two methods , methods of part 1 is a comparison of the results with the thermal management simulation and experiment, part 2 is a method of optimizing the thermal management for battery pack by using solidwork software. When the fan is on, the forced air flow over the cells removes some of the generated heat. Results of method part 1 is simulation more heat than experiment in the amount of 0.11% – 1.56%. The results of the method part 2 is simulated using the fan 4 fan with a speed of 415 rad/s and battery gap 30mm most efficient compared with 4 fans the other , while the simulation using 6 fan, fan speed 415 rad/s and battery gap 30mm most efficient for all.